Spiritualitas Penyembuh Jiwa: Dzikrullah sebagai Islamic Coping Mechanism Perspektif Surah Ar-Ra’d Ayat 28 - Abid Ihsan Alfaruq; Yeti Dahliana (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
Mental health is a global issue that is increasingly gaining attention, particularly in the context of emotional and psychological disorders affecting many individuals. One way to manage mental health issues is by utilizing coping mechanisms or coping strategies. In Islam, dzikrullah (remembrance of Allah) can serve as an Islamic coping mechanism, representing a coping strategy from an Islamic perspective. Surah Ar-Ra'd verse 28 serves as the primary foundation for understanding peace of mind within an Islamic framework. Through a literature review and content analysis of Lazarus and Folkman's coping theory, Kenneth I. Pargament's concept of religious coping, alongside the interpretations of classical and contemporary scholars regarding Surah Ar-Ra'd verse 28, this research demonstrates that dzikrullah functions as a form of emotion-focused coping. It regulates the cognitive appraisal of stress, soothes emotions, and reinforces spiritual meaning when confronting life's trials. The findings of this study indicate differences in the forms of dzikrullah based on the interpretations of classical and contemporary scholars; however, both find common ground in that the core concept of dzikrullah is a way of life that brings inner peace. This article concludes that dzikrullah holds significant potential as a relevant Islamic coping mechanism to enhance resilience and mental well-being amidst the modern mental health crisis.